Emergency Physician and Advanced Practice Provider Diagnostic Testing and Admission Decisions in Chest Pain and Abdominal Pain. (21st November 2020) - Pines, Jesse M.; Zocchi, Mark S.; Ritsema, Tamara S.; Bedolla, John; Venkat, Arvind; ,
Abstract: Objective: We compare utilization of diagnostic resources and admissions in emergency department (ED) patients with chest pain and abdominal pain when managed by advanced practice providers (APPs) and physicians. Methods: We used 2016 to 2019 data from a national emergency medicine group. We compared visits managed by physicians and APPs based on demographics and observed resource utilization (labs, radiography, computed tomography) use and hospital admission/transfer, stratified by patient age. To reduce selection bias, we created inverse propensity score weights (IPWs). To estimate the average treatment effect for APP visits for each outcome, we included IPWs in a multivariable linear probability model with a dummy variable indicating treatment by an APP and used a facility fixed effect. We then estimated the average treatment effect comparing physician to APP visit for all visits and for discharged visits separately, stratified by the study outcomes. Sensitivity analyses were performed using different cohort definitions and adjusting for past medical history. Results: In chest pain, we included 77, 568 visits seen by 1, 011 APPs and 586, 031 visits seen by 1, 588 physicians. In abdominal pain, we included 184, 812 ED visits seen by 1, 080 APPs and 761, 230 visits seen by 1, 689 physicians. For both chest pain and abdominal pain visits, physicians saw more older adult patients (55+ years) and admitted a higher percentage of visits than APPs. For chest pain, physicians saw more circulatory system diseases (70.7% vs. 58.6%); APPs saw more respiratory system diseases (17.1% vs. 9.8%). In abdominal pain, emergency physicians saw more digestive system diseases (28.5% vs. 23.3%); APPs saw more genitourinary system diseases. After matching with IPW, predicted probabilities of laboratory, radiology, and admissions either did not vary or were slightly lower for APPs compared to physicians for all outcomes. Sensitivity analyses showed similar results, including controlling for past medical history. Conclusion: Diagnostic testing and hospitalization rates for chest pain and abdominal pain between APPs and physicians is largely similar after matching for severity and complexity. This suggests that APPs do not have observably higher use of ED and hospital resources in these conditions in this national group.